IMPLEMENTASI PENERAPAN SANKSI OLEH BPJS KETENAGAKERJAAN CABANG SURABAYA RUNGKUT TERHADAP PERUSAHAAN YANG MENDAFTARKAN SEBAGIAN PEKERJANYA KE BPJS KETENAGAKERJAAN - Firlizalsyah, Farel; Nugroho, Arinto (NOVUM : JURNAL HUKUM)
Social security administered by the Social Security provider of human resources (BPJS Employment) is a program created by the government as a legal protection effort for workers. Companies that register some of their workers with BPJS Ketenagakerjaan are deemed not in accordance with the provisions in Article 15 of Law Number 24 of 2011 about BPJS. Partial Registered Company (PDS) of Workers is one example of violations comitted in article 32 paragraph (3) of Government Regulation Number 44 of 2015 about the implementation of work accident and death insurance programs. As a result, the benefits of the social security program cannot be claimed by unregistered workers. This research aims to analyze the law enforcement that is applied by the BPJS Employment Surabaya Rungkut branch in dealing with companies that register some of their workers with BPJS Employment. This research is Empirical Juridical research with analysis using qualitative descriptive techniques. Based on the results, the implementation of administrative sanctions carried out by BPJS Employment Surabaya Rungkut branch is under applicable regulations, and the implementation of efforts to deal with PDS of workers has been carried out properly